2009
DOI: 10.1007/s10802-009-9349-6
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Depression, Maternal Expressed Emotion, and Youth Psychopathology

Abstract: Across development, maternal depression has been found to be a risk factor for youth psychopathology generally and youth depression specifically. Maternal Expressed Emotion (EE) has been examined as a predictor of outcome among youth with depression. The present study explored the associations between youth psychopathology and two predictors-maternal depression within the child's lifetime and maternal EE-in a study of children at risk for depression. One hundred and seventy-one youth, ages 8-12, and their moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
71
2
21

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 69 publications
5
71
2
21
Order By: Relevance
“…Given the high rates of maternal EE observed in this sample, they are particularly sobering. Indeed, we found that 55% of mothers were high in EE, a rate that outpaces findings from research on pediatric bipolar disorder (46%; Sullivan & Miklowitz, 2010), and high risk children youth (25%; Tompson et al, 2010). Our prevalence rate roughly corresponds to rates of EE found in families of youth with ADHD (52%; Asarnow et al, 2001) and families of youngsters with intellectual disabilities (60%; Beck, Daley, Hastings & Stevenson, 2004).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Given the high rates of maternal EE observed in this sample, they are particularly sobering. Indeed, we found that 55% of mothers were high in EE, a rate that outpaces findings from research on pediatric bipolar disorder (46%; Sullivan & Miklowitz, 2010), and high risk children youth (25%; Tompson et al, 2010). Our prevalence rate roughly corresponds to rates of EE found in families of youth with ADHD (52%; Asarnow et al, 2001) and families of youngsters with intellectual disabilities (60%; Beck, Daley, Hastings & Stevenson, 2004).…”
Section: Discussionsupporting
confidence: 61%
“…Although additional work examining EE in the context of pediatric OCD has been slow to emerge, a handful of studies have examined parental psychopathology as a correlate of EE in other pediatric psychiatric populations (Tompson, Pierre, Boger, McKowen, Chan & Freed, 2010). These studies paint a mixed picture, with some suggesting that a history of maternal depression is associated with high maternal EE (Bolton, Calam, Barrowclough, Peters, Roberts, Wearden & Morris, 2003; Tompson et al, 2010) and others failing to find these links (Goldstein, Miklowitz, & Richards, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Family relationships and parenting factors including warmth/hostility, attachment, criticism, and parents' coping are possible contributors to children's mood symptoms. 5,[13][14][15][16] High levels of criticism in parent-child relationships are associated with lower child social competence, depressive symptoms, and suicidal ideation. 15,16 Several psychotherapeutic interventions have been developed to address these factors.…”
Section: Family Functioning and Childhood Mood Disordersmentioning
confidence: 99%
“…For example, children of depressed parents were more likely to show depressive symptoms where high parental expressed emotion acted as a stressor for the child (150,177). However, contrary to the evidence above about conflict, a recent analysis of data from the Minnesota Twin study suggested that life stressors outside the family (so excluding divorce) were more likely to be associated with internalising disorders at age 17 than were problematic parent relationships (178).…”
Section: Stressmentioning
confidence: 92%